Two New Species of Myrcia (Myrtaceae) from Brazil - Faria, Jair E. Q.; Lucas, Eve J.; Sobral, Marcos (Phytotaxa, 2017)
Two new species of Myrcia from the Brazilian Cerrado are described: Myrcia occulta and Myrcia matogrossensis. Notes on species morphology, phenology and conservation status are provided as well as illustrative plates and distribution maps.